INCOME ANALYSIS OF PIG FARMING BUSINESS “RED PIG FARM” IN PANGOLOMBIAN VILLAGE, SOUTH TOMOHON DISTRICT, TOMOHON CITY - Sumule, Asri Intan; Lumenta, Ingriet; Lainawa, Jolyanis; Moningkey, Sony A. E.; Oroh, Franky N. S. (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2025)
This study aims to describe and analyze the Red Pig Farm business. This study uses a survey method through a case study approach on Mr. Ferry Wawo's pig farming business. Uses a quantitative descriptive method. The data collection period is from April 2024 - April 2025. The results of this study indicate that the Red Pig Farm has implemented good technical aspects such as feeding, maintenance management, housing, and disease prevention and this pig farming business provides income. Where production costs consist of fixed costs and variable costs as well as total costs, where fixed costs consist of; depreciation costs for cages and equipment, and tax costs for one year amounting to Rp42,897,143, for variable costs Rp244,203,043, the total cost of the Red Pig Farm livestock business for one year amounting to Rp287,100,186. The income of the Red Pig Farm livestock business for one year of production period is obtained from the sale of pigs and livestock that have not been sold (stock) where the number of livestock sold is 64 and livestock that have not been sold is 49 with a total value of Rp830,350,000. For the income of Red Pig Farm for one year amounting to Rp543,567,814. For the level of profit or income from the Red Pig Farm livestock business, based on the results of the R/C ratio analysis, the value obtained was 2.90 or RC ratio 1, so the business run by Mr. Ferry Wawo made a profit. The conclusion is that the Red Pig Farm pig farming business in Kelurahan Pangolombian, South Tomohon District, Tomohon City, is still able to demonstrate good performance and survive after the ASF virus outbreak, while also generating adequate income and having good prospects for future development.